A low cost - high accuracy multisensor array for bat localization - Hochradel, Klaus; Dorsch, Philipp; Häcker, Timm; Hohler, Tino; Sutor, Alexander; Lerch, Reinhard (International Bat Research Conference, 2016)
Many behavioral studies demand knowledge of the distribution or location of bats in space. Our research group investigated the behavior of bats in close proximity to the nacelle of wind turbines. Therefore, we measured the distribution of bats with help of stereo infrared cameras. Systems able to provide this information are expensive, complicated and require a specialist in the field for assembly and data acquisition. Our aim was to design an inexpensive and easy to use system to localize bats that, in addition, allows long recording periods. In order to gain maximum information the localization system contains different sensor technologies. On one hand, it includes active infrared-stereo-cameras to localize bats optically and on the other hand each ultrasonic bat call can be recorded and localized by multilateration with multiple novel ultrasonic microphones. We developed a calibration procedure to align the optical and the acoustical system. The developed setup with its dimension of 1x1m is tripod mountable and the costs sum up to 5000 EUR with the goal to decrease costs to 2000 EUR. To achieve this, we programmed a FPGA to record the ultrasonic bat signals to be independent of proprietary hardware. Furthermore, we implemented a novel detection algorithm for ultrasonic bat calls which allows to run different detection techniques simultaneously in real-time. This algorithm was optimized for the FPGA and provides precise distinction between bat calls and noise to reduce post processing efforts and disk space. Both systems offer an accuracy of ±20 cm within a radius of 20 m. Since the optical and the acoustical system are calibrated, their results can be combined to improve not only accuracy but also reliability.
Keywords: Microphone Array; Bat; Localization; Stereo Camera

Fehlerbetrachtung und Kalibrierung eines portablen Mikrofonarrays zur multilateralen Ortung von Ultraschall-Fledermausrufen - Hochradel, Klaus; Dorsch, Philipp; Häcker, Timm; Sutor, Alexander; Lerch, Reinhard (DAGA - 42. Jahrestagung für Akustik, 2016)
Keywords: Microphone Array; Stereo Camera; Calibration

Three-dimensional localization of bats: visual and acoustical - Hochradel, Klaus; Häcker, Timm; Hohler, Tino; Becher, Andreas; Wildermann, Stefan; Sutor, Alexander (IEEE Sensors Journal, 2019)
Keywords: Acoustics; Cameras; Microphone arrays; Hardware; Sensors; Data acquisition; Microphone; Array; Stereo Camera; Infrared; automation; Ultrasound; Source localization; Bat